Benefits, Barriers and Outcomes of Older Adults Undertaking a Facility-Based Transition Care Program - Hang, Jo-Aine (Curtin University, 2021)
The research evaluated the impact of transition care programs on older adults’ health and wellbeing by determining the health-related outcomes and the benefits, barriers and enablers for older adults undertaking these programs. Research findings demonstrated that facility-based transition care outcomes vary internationally. Older adults undertaking transition care in a facility in Western Australia demonstrated improved health outcomes. However, some functional deficits persisted and more emotional support to improve older adults’ transition care experience is required.